Konsep Kepribadian Guru: Perspektif Historis - Isti'anah Abubakar (UIN Maulana Malik Ibrahim Malang, 2006)
Teaching is perceived as a very heavy duty, but for other, teaching is the art and full charity. Teacher is person who teaches pupils to rich their best life. However, public does not care about the teaching profession. New generations are seemingly not interested in this profession. Lack in prosperity of teacher's life is the main factors of public's undesirable to the teaching profession which becomes a problem. Based on the phenomenon, there are many ways to undertake. One of them is Public Regulation of Teaching Profession (UU No. 14, 2005). The regulation is not the mere solution, yet, it is recommended that teacher's personality and performance have to improve to the ideal one. This paper offers the effort which is based on qonaah and commitment. It means that teachers should not be passive by encouraging themselves to conduct classroom action research. In addition, teachers should uphold their commitment to improve their integrity as professional teacher. Pengajaran dianggap sebagai tugas yang sangat berat, tapi bagi yang lain, pengajaran adalah seni dan amal penuh. Guru adalah orang yang mengajarkan murid untuk kaya dengan kehidupan terbaik mereka. Namun, masyarakat tidak peduli dengan profesi mengajar. Generasi baru nampaknya tidak tertarik dengan profesi ini. Kurangnya kemakmuran hidup guru merupakan faktor utama yang tidak diinginkan masyarakat terhadap profesi mengajar yang menjadi masalah. Berdasarkan fenomena tersebut, ada banyak cara untuk melakukan. Salah satunya adalah Peraturan Umum Profesi Pengajaran (UU No. 14, 2005). Peraturannya bukanlah solusi belaka, namun, disarankan agar kepribadian dan kinerja guru harus ditingkatkan sesuai keinginan. Makalah ini menawarkan usaha yang didasarkan pada qonaah dan komitmen. Artinya, guru tidak boleh bersikap pasif dengan mendorong diri mereka untuk melakukan penelitian tindakan kelas. Selain itu, guru harus menjunjung tinggi komitmen mereka untuk meningkatkan integritas mereka sebagai guru profesional.